E-book for database subject / Aznira Abdullah Zawawi - Abdullah Zawawi, Aznira (2007)
This research project is about developing e-books for database subject using interactive querying technique. This research is concerned with the development of electronic book for the database subject which is one of the disciplines in the computer science. This e-book should be used as a tool in learning the database subject and specifically in the queries language. In this e-book I also use the Query-by-Browsing tools in applying the interactive querymg. The objectives of this research are to identify the design criteria for e-books and to demonstrate ebook for database subject using interactive querying findings section. The e-book is developing using Microsoft Frontpage as the interface design and compile into e-book using E-book Maestro Free. In the end of research project period, researcher found that the result is complying with the objectives and therefore all the objectives in this research project have been achieved.